Who$1 (Bs to Blame for Greece?s Austerity in Charge of Saving a Broken Economy - Pelagidis, Theodore; Mitsopoulos, Michael; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
Greece's economy symbolizes in many ways the Eurozone's economic problems and divergent interests as it amasses most of the economic disadvantages characterizing the Eurozone's economy itself. This book presents the economic and political challenges to Greece and the EU member states.
Keywords: Finance, Public; Political economy; Macroeconomics; International economics; Economic policy; Economic history; Economics; Macroeconomics/Monetary Economics//Financial Economics; International Economics; Economic Policy; Public Finance; Economic History; Political Economy; Electronic books